2016
DOI: 10.1186/s13059-016-1014-0
|View full text |Cite
|
Sign up to set email alerts
|

The mRNA-bound proteome of the human malaria parasite Plasmodium falciparum

Abstract: BackgroundGene expression is controlled at multiple levels, including transcription, stability, translation, and degradation. Over the years, it has become apparent that Plasmodium falciparum exerts limited transcriptional control of gene expression, while at least part of Plasmodium’s genome is controlled by post-transcriptional mechanisms. To generate insights into the mechanisms that regulate gene expression at the post-transcriptional level, we undertook complementary computational, comparative genomics, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
80
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(86 citation statements)
references
References 78 publications
5
80
0
1
Order By: Relevance
“…One explanation is that they are a normal byproduct of promoter activity, similar to that described previously for higher eukaryotes (57) . A second explanation is that these transcripts have some function in gene regulation, which we speculate could include binding by regulatory proteins containing an RNA recognition motif (RRM), many of which are encoded in the P. falciparum genome (66) , but which are largely uncharacterised (67) . Additionally, our identification of independently regulated ncRNAs may help future studies of gene regulation, as seen with an ncRNA antisense to GDV1 (68) (which can be observed in our data, Figure S27 ), which is involved in the regulation of sexual commitment.…”
Section: Discussionmentioning
confidence: 99%
“…One explanation is that they are a normal byproduct of promoter activity, similar to that described previously for higher eukaryotes (57) . A second explanation is that these transcripts have some function in gene regulation, which we speculate could include binding by regulatory proteins containing an RNA recognition motif (RRM), many of which are encoded in the P. falciparum genome (66) , but which are largely uncharacterised (67) . Additionally, our identification of independently regulated ncRNAs may help future studies of gene regulation, as seen with an ncRNA antisense to GDV1 (68) (which can be observed in our data, Figure S27 ), which is involved in the regulation of sexual commitment.…”
Section: Discussionmentioning
confidence: 99%
“…Applied to HeLa and HEK293 cells, RNA interactome capture identified more than a thousand RBPs, hundreds of which were previously unknown to bind RNA. This method was successfully used to determine the poly(A)-RNA-binding proteome of different human cell types, including human (Baltz et al 2012;Castello et al 2012;Beckmann et al 2015) and murine (Kwon et al 2013;Liao et al 2016;Liepelt et al 2016) cells, as well as from organisms such as S. cerevisiae (Mitchell et al 2013;Beckmann et al 2015;Matia-González et al 2015), C. elegans (Matia-González et al 2015), D. melanogaster (Sysoev et al 2016;Wessels et al 2016), A. thaliana (Marondedze et al 2016;Reichel et al 2016), and the parasites plasmodium and trypanosoma (Bunnik et al 2016;Lueong et al 2016). However, the identification of the RBPs bound to specific RNAs remains challenging.…”
Section: Introductionmentioning
confidence: 99%
“…In a related study, it was further shown that a messenger ribonucleoprotein (mRNP) from P. berghei gametocytes contains DOZI and the Sm‐like factor CITH (homolog of worm CAR‐I and fly Trailer Hitch) . The composition analysis of mRNP complex indicated that it contains 16 major protein factors including eIF4E and poly(A)‐binding protein . During the intraerythrocytic developmental cycle, numerous RNA‐binding proteins including DOZI have been reported to be implicated in post‐transcriptional regulation of gene expression .…”
Section: Dead‐box Helicases Of Plasmodium Falciparummentioning
confidence: 99%